Prevalence of Acute Deep Vein Thrombosis in Patients with Ankle and Foot Fractures Treated with Nonoperative Management—A Pilot Study - Ho, Edward; Omari, Abdullah (International Journal of Angiology, 2017)
The prevalence of deep vein thrombosis (DVT) among patients with ankle and foot fractures in Australia treated nonsurgically is unknown. Indications for thromboprophylaxis screening and management are unclear.The primary outcome was the prevalence rate of DVT among nonsurgically managed ankle and foot fracture patients. Patients were enrolled into a prospective cross-sectional pilot study at an outpatient hospital fracture clinic. DVT risk factors and symptoms were recorded at time of recruitment followed by referral for compression duplex ultrasonography. Independent t-test and Fisher exact test were used to assess the significance of these variables with DVT.A total of 72 patients were included in the final analysis. Overall, 11% (8/72) of patients had DVT—seven distal DVTs and one proximal DVT. Four were symptomatic including the patient with a proximal thrombus. In comparison, the majority of patients were asymptomatic of DVT (63/72). A significant risk factor found to be associated with DVT was age ≥ 45 (p = 0.013) years, and a lack of symptoms (p = 0.006) was associated with no DVT.This pilot study is the first in Australia to investigate the prevalence of DVT in this specific subgroup of patients. We found a prevalence of 11% of DVT in a small group of patients with age ≥ 45 years, being the only significant associated risk factor. Future larger scale prospective studies are warranted to confirm these results.
Keywords: deep vein thrombosis; duplex; ultrasound; lower extremity; proximal; distal